EFEITOS CARDIOVASCULARES DA INIBIÇÃO DA CICLOOXIGENASE-2 EM UM MODELO EXPERIMENTAL DE PERIODONTITE INDUZIDA POR LIGADURA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
Periodontal disease is an inflammatory chronic disorder caused by a small group of gram-negatives bacteria witch colonizes the subgengival area. This disease is characterized by the destruction of the periodontal tissues, including bone resorption and loss of clinical attachment level. Observational studies have shown an increase in the risk of cardiovascular diseases, specially atherosclerosis and hypertension, among the subjects affected by the periodontal disease. The literature also reports endothelial dysfunction among these patients. Data suggest that the systemic inflammation due to the biofilm present in periodontits and the reduction in the nitric oxide availability may be, at least in part, the cause of endothelial dysfunction, which leads to cardiovascular disorders. An increase in vascular COX-2 expression has been demonstrated among diseases related to endothelial dysfunction. COX-2 expression seems to have an important protector function through the production of arachidonic acid metabolites with vasodilator and antitrombotic properties. Therefore, COX-2 inhibition may represent negative cardiovascular implications. The purpose of this research was to evaluate the effect of COX-2 inhibition on the vascular reactivity and on the heart tissue of animals with periodontitis. At day 0, Wistar rats were subdivided into the following groups: ligature + etoricoxib (the animals received ligatures and were treated with etoricoxib 10 mg/kg p.o., for seven days, from the day 14), ligature + vehicle (the animals were treated with distilled water), sham + etoricoxib (the animals went through a sham procedure: the ligatures were positioned and immediately removed) and sham + vehicle. The rats were prepared for the data collection and sacrificed at day 21. Changes on the vasoconstrictor response were not observed. However, the group ligature + etoricoxib showed a tendency to have the vasodilator response reduced. All the groups showed histological cardiac alterations, especially the groups that received etoricoxib, when submitted to ischemia with isoprenaline. It is suggested, though, that COX-2 inhibition in an experimental model of periodontal disease may increase cardiovascular disorders.
Cardiovascular Effects of the Cyclooxygenase-2 Inhibition in an Experimental Model of Periodontitis in Rats
Keywords: Periodontite; Ciclooxigenase-2; Endotélio Vascular; Periodontitis; Cyclooxygenase-2; Vascular Endothelium; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA